السؤال
الحل
y − 5 y + 1 + y − 1 y + 5 − 25 y 2 + 6 y + 5
y − 5 y + 1 + y − 1 y + 5 − 25 y 2 + 6 y + 5 = y − 5 y + 1 + y − 1 y + 5 − 25 ( y + 1 ) ( y + 5 ) = ( y − 5 ) ( y + 5 ) + ( y − 1 ) ( y + 1 ) − 25 ( y + 1 ) ( y + 5 ) = y 2 − 25 + y 2 − 1 − 25 ( y + 1 ) ( y + 5 ) = 2 y 2 − 51 ( y + 1 ) ( y + 5 )
x+512x×6x−30x2−25=x+512x×6(x−5)(x−5)(x+5)=12x
3−x4−2x×x2+x−69−x2=3−x−2(x−2)×(x+3)(x−2)(3−x)(3+x)=−12
y2−7yy3−27÷y2−49y2+3y+9=y(y−7)(y−3)(y2+3y+9)×y2+3y+9(y−7)(y+7)=y(y−3)(y+7)
5x2−36−2x2−12x+36=5(x−6)(x+6)−2(x−6)2=5(x−6)−2(x+6)(x−6)2(x+6)=5x−30−2x−12(x−6)2(x+6)=3x−42(x−6)2(x+6)
3x−2−2x−2+4+2x+x2x3−8=1x−2+4+2x+x2(x−2)(x2+2x+4)=1+1x−2=2x−2
تم حفظ السؤال في محفظة الأسئلة
لايمكن حفظ السؤال لانه خارج الصف المحدد من قبلكم